Functional conservation of the fruitless male sex-determination gene across 250 Myr of insect evolution. - Gailey, D; Billeter, J; Liu, J; Bauzon, F; Allendorfer, J; Goodwin, S (2006)
Male sexual behavior in the fruit fly Drosophila melanogaster is regulated by fruitless (fru), a sex-determination gene specifying the synthesis of BTB-Zn finger proteins that likely function as male-specific transcriptional regulators. Expression of fru in the nervous system specifies male sexual behavior and the muscle of Lawrence (MOL), an abdominal muscle that develops in males but not in females. We have isolated the fru ortholog from the malaria mosquito Anopheles gambiae and show the gene's conserved genomic structure. We demonstrate that male-specific mosquito fru protein isoforms arise by conserved mechanisms of sex-specifically activated and alternative exon splicing. A male-determining function of mosquito fru is revealed by ectopic expression of the male mosquito isoform FRUMC in fruit flies; this results in MOL development in both fru-mutant males and fru+ females who otherwise develop no MOL. In parallel, we provide evidence of a unique feature of muscle differentiation within the fifth abdominal segment of male mosquitoes that strongly resembles the fruit fly MOL. Given these conserved features within the context of 250 Myr of evolutionary divergence between Drosophila and Anopheles, we hypothesize that fru is the prototypic gene of male sexual behavior among dipteran insects.